Research on Performance Optimization of Running Air-cooled Heat Pipe Radiator Based on Temperature Equalization Technology - Zhiyong WU; Xiong WANG; Nan HUANG; Guomeng SONG; Hongfeng WANG; Mingyi CHEN; Jie ZOU (机车电传动)
In view of the high risk of overheat for traditional air-cooled straight pipe heat pipe radiators in the low-speed operation of subway, a new type of heat pipe radiator that can effectively solve the problem above was proposed. Based on the temperature equalization technology, the application of numerical simulation and experimental testing methods, L-shaped heat pipes and temperature equalization pipes was used to achieve optimization on the basis of the original straight heat pipe radiator, and fi eld test veri fi cation was conducted on the subway line. The results showed that the application of L-shaped heat pipe radiator with equalizing temperature tube can effectively solve the problem of overheating in low-speed operation, which can be adapted to all working conditions, ensure the weight reduction and ef fi ciency increase on the premise of safety